Sociological–Legal Aspects of Prenatal Diagnostics and the Awareness of Citizens of Kosovska Mitrovica about Prenatal Diagnostics - Kostić, Ana Z.; Tomašević, Milica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
For parents, and especially for mothers, as well as for medical staff and the wider social community, the health of the child is of paramount importance. Accordingly, it is essential to monitor the health of the pregnant woman and the fetus, to identify high-risk pregnancies in a timely manner, and to provide support, counseling, and information to future parents. Prenatal diagnostics comprise a set of medical procedures performed during pregnancy in order to assess the health and development of the unborn child. This process is undoubtedly a delicate and complex aspect of medicine, the use of which should be carefully considered in consultation with the medical team and with due regard to ethical and moral principles.This paper presents the results of both theoretical and empirical research on the complex procedure of prenatal diagnostics, the individual methods employed within it, and their aim of ensuring the birth of a healthy and viable child. Particular attention is given to the decision-making process of parents when fetal anomalies are diagnosed. The intention is to highlight the complexity of parental decision-making regarding pregnancy outcomes in such situations.Citizens’ awareness of the procedures at the Clinical and Hospital Center of Kosovska Mitrovica was the subject of empirical investigation. The survey method was applied, involving 107 respondents, citizens of Kosovska Mitrovica, who completed a non-standardized questionnaire constructed for the purposes of this research. The theoretical review of the scientific literature analyzed available methods and procedures, social opportunities and conditions, public awareness of the importance of prenatal diagnostics, and measures aimed at improving standards, all with the goal of providing better conditions and social treatment for pregnant women, children, and families as a whole. The initial hypothesis was that citizens of Kosovska Mitrovica are not sufficiently informed about prenatal diagnostics.
Keywords: prenatal diagnostics; social opportunities; legal regulation; family; Kosovska Mitrovica